RUNX proteins in development and cancer - Groner, Yoram ; Ito, Yoshiaki ; Liu, Pu Paul ; Neil, James C. ; Speck, Nancy A ; Van Wijnen, Andre J. (Springer, 2020)
This volume provides the reader with an overview of the diverse functions of the RUNX family of genes. As highlighted in the introduction and several of the 29 chapters, humans and other mammals have three RUNX genes that are known to play specific roles in blood, bone and neuronal development. However, their evolutionary history has recently been traced back to unicellular organisms and their involvement in many well-known signaling pathways (Wnt, TGFb, Notch, Hippo) is indicative of a more general function in cell biology. Their documented roles in cell fate decisions include control of proliferation, differentiation, survival, senescence and autophagy--Publisher's description.Evolution of RUNX genes. RUNX in invertebrates / S. Hughes, A. Woollard -- RUNX and CBF[beta] structure and biophysics of CBF[beta]/RUNX and its translocation products / Tahir H. Tahirov, John Bushweller -- Covalent modifications of RUNX proteins: structure affects function / Ezra Blumenthal, Sarah Greenblatt, Guang Huang, Koji Ando, Ye Xu, Stephen D. Nimer -- RUNX genes and mammalian development. The role of Runx1 in embryonic blood cell formation / Amanda D. Yzaguirre, Marella F.T.R. de Bruijn, Nancy A. Speck -- Runx1 structure and function in blood cell development / Constanze Bonifer, Elena Levantini, Valerie Kouskoff, Georges Lacaud -- Roles of Runx2 in skeletal development / Toshihisa Komori -- Mitotic gene bookmarking: an epigenetic mechanism for coordination of lineage commitment, cell identity and cell growth / Sayyed K. Zaidi, Jane B. Lian, Andre van Wijnen, Janet L. Stein, Gary S. Stein -- Roles of Runx genes in nervous system development / Jae Woong Wang, Stefano Stifani -- Runx family genes in tissue stem cell dynamics / Chelsia Qiuxia Wang, Michelle Meng Huang Mok, Tomomasa Yokomizo, Vinay Tergaonkar [and others] -- Roles of the RUNX1 enhancer in normal hematopoiesis and leukemogenesis / Wei-Siang Liau, Phuong Cao Thi Ngoc, Takaomi Sanda -- RUNX1 and CBF[beta] fusion proteins in leukemia. RUNX1-ETO leukemia / Shan Lin, James C. Mulloy, Susumu Goyama -- Clinical relevance of RUNX1 and CBFB alterations in acute myeloid leukemia and other hematological disorders / Klaus H. Metzeler, Clara D. Bloomfield -- Mechanism of ETV6-RUNX1 leukemia / Aishwarya Sundaresh, Owen Williams -- ETV6-RUNX1 + acute lymphoblastic leukaemia in identical twins / Anthony M. Ford Ph. D., Mel Greaves FRS -- Molecular basis and targeted inhibition of CBF[beta]-SMMHC acute myeloid leukemia / Lucio H. Castilla, John H. Bushweller -- RUNX and CBF[beta] in cancer and immune function. The RUNX genes as conditional oncogenes: insights from retroviral targeting and mouse models / James C. Neil, Kathryn Gilroy, Gillian Borland, Jodie Hay, Anne Terry, Anna Kilbey -- RUNX1 and CBF[beta] mutations and activities of their wild-type alleles in AML / R. Katherine Hyde, Paul Liu, Alan D. Friedman -- Roles of RUNX in B cell immortalisation / Michelle J. West, Paul J. Farrell -- Roles of RUNX in Solid Tumors / Linda Shyue Huey Chuang, Kosei Ito, Yoshiaki Ito -- RUNX3 and p53: how two tumor suppressors cooperate against oncogenic ras? / Jung-Won Lee, Andre van Wijnen, Suk-Chul Bae -- RUNX and CBF[beta] in cancer and immune function. Runx3 and cell fate decisions in pancreas cancer / Martin C. Whittle, Sunil R. Hingorani -- Runx genes in breast cancer and the mammary lineage / Nicholas Rooney, Alessandra I. Riggio, Daniel Mendoza-Villanueva, Paul Shore [and others] -- Runx3 in immunity, inflammation and cancer / Joseph Lotem, Ditsa Levanon, Varda Negreanu, Omri Bauer, Shay Hantisteanu [and others] -- Roles of RUNX complexes in immune cell development / Takashi Ebihara, Wooseok Seo, Ichiro Taniuchi -- CBF[beta] and HIV infection / Dong Young Kim, John D. Gross -- Emerging roles for RUNX. Roles of RUNX in hippo pathway signaling / Antonino Passaniti, Jessica L. Brusgard, Yiting Qiao, Marius Sudol [and others] -- Roles of RUNX in hypoxia-induced responses and angiogenesis / Sun Hee Lee, Sarala Manandhar, You Mie Lee -- The emerging roles of RUNX transcription factors in epithelial-mesenchymal transition / Dominic Chih-Cheng Voon, Jean Paul Thiery -- A regulatory role for RUNX1, RUNX3 in the maintenance of genomic integrity / Vaidehi Krishnan, Yoshiaki Ito.